Comparison of nanopore with illumina whole genome assemblies of the Epstein-Barr virus in Burkitt lymphoma - Isaac E. Kim; Abebe A. Fola; Enrique Puig; Titus Kipkemboi Maina; Sin Ting Hui; Hongyu Ma; Kaleb Zuckerman; Eddy O. Agwati; Alec Leonetti; Rebecca Crudale; Micah A. Luftig; Ann M. Moormann; et al. (Scientific Reports)
Abstract Endemic Burkitt lymphoma (eBL) is one of the most prevalent cancer in children in sub-Saharan Africa, and while prior studies have found that Epstein-Barr virus (EBV) type and variation may alter the tumor driver genes necessary for tumor survival, the precise relationship between EBV variation and EBV-associated tumorigenesis remains unclear due to lack of scalable, cost-effective, viral whole-genome sequencing from tumor samples. This study introduces a rapid and cost-effective method of enriching, sequencing, and assembling accurate EBV genomes in BL tumor cell lines through a combination of selective whole genome amplification (sWGA) and subsequent 2-tube multiplex polymerase chain reaction along with long-read sequencing with a portable sequencer. The method was optimized across a range of parameters to yield a high percentage of EBV reads and sufficient coverage across the EBV genome except for large repeat regions. After optimization, we applied our method to sequence 18 cell lines and 3 patient tumors from fine needle biopsies and assembled them with median coverages of 99.62 and 99.68%, respectively. The assemblies showed high concordance (99.61% similarity) to available Illumina-based assemblies. The improved method and assembly pipeline will allow for better understanding of EBV variation in relation to BL and is applicable more broadly for translational research studies, especially useful for laboratories in Africa where eBL is most widespread.